Pengaruh Kinerja Keuangan dan Inflasi terhadap Harga Saham (Studi Pada perusahaan Sektor Barang Konsumsi yang terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Widati, Sri (Jurnal Ilmiah Dikdaya, 2022)
This study aims to determine the effect of financial performance and inflation on stock prices (a study of consumer goods sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period). The population in this study amounted to 47 consumer goods sector companies listed on the Indonesian stock exchange. With the sampling technique using a purposive sampling technique with certain criteria, so that the sample in this study amounted to 28 companies. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that the variable ROA has a positive and significant effect on stock prices, NPM has a positive and insignificant effect on stock prices, DAR has a negative and significant effect on stock prices, PER has a positive and significant effect on stock prices, and finally inflation has a positive and no effect significant to the Share Price.